Trouble shooting during bioanalytical estimation of drug and metabolites using LC-MS/MS: A review - Ganesh N Sharma; Man Mohan Singhal; K K Sharma; Jyotsana Sanadya (Wolters Kluwer Medknow Publications, 2010)
Bioanalysis frequently involves the measurement of very low analyte concentrations in complex and potentially variable matrices. An initial attempt has been made to apply a risk management tool to the bioanalytical method development like selection of spiked plasma volume, selection of internal standard to minimize processing error, selection of medium and extraction procedure, setting of mobile phase and pH, determination of chromatographic conditions etc. and to minimize instrumental error like; ion suppression and matrix effect.